2022
DOI: 10.1098/rspb.2022.1123
|View full text |Cite
|
Sign up to set email alerts
|

Long-term changes in avian biomass and functional diversity within disturbed and undisturbed Amazonian rainforest

Abstract: Recent long-term studies in protected areas have revealed the loss of biodiversity, yet the ramifications for ecosystem health and resilience remain unknown. Here, we investigate how the loss of understory birds, in the lowest stratum of the forest, affects avian biomass and functional diversity in the Amazon rainforest. Across approximately 30 years in the Biological Dynamics of Forest Fragments Project, we used a historical baseline of avian communities to contrast the avian communities in today's primary fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 94 publications
0
7
0
Order By: Relevance
“…Conservation.-Long-term studies of tropical forest bird communities have demonstrated losses of functional and taxonomic diversity in both disturbed (Palacio et al 2019, Gómez et al 2021, Luther et al 2022) and undisturbed landscapes (Blake & Loiselle 2015), but the forest avifauna we describe appears largely intact, suggesting the area still presents a valuable opportunity for conservation. For example, large-bodied, terrestrial species sensitive to local extirpation from hunting pressure (Peres 2001) including Psophia crepitans, Mitu salvini and Nothocrax urumutum are regularly recorded by camera-traps (Table 1).…”
Section: Red-crested Finch Coryphospingus Cucullatusmentioning
confidence: 77%
“…Conservation.-Long-term studies of tropical forest bird communities have demonstrated losses of functional and taxonomic diversity in both disturbed (Palacio et al 2019, Gómez et al 2021, Luther et al 2022) and undisturbed landscapes (Blake & Loiselle 2015), but the forest avifauna we describe appears largely intact, suggesting the area still presents a valuable opportunity for conservation. For example, large-bodied, terrestrial species sensitive to local extirpation from hunting pressure (Peres 2001) including Psophia crepitans, Mitu salvini and Nothocrax urumutum are regularly recorded by camera-traps (Table 1).…”
Section: Red-crested Finch Coryphospingus Cucullatusmentioning
confidence: 77%
“…2019, Gómez et al . 2021, Luther et al . 2022) and undisturbed landscapes (Blake & Loiselle 2015), but the forest avifauna we describe appears largely intact, suggesting the area still presents a valuable opportunity for conservation.…”
Section: Discussionmentioning
confidence: 99%
“…Although there can be different responses to species abundance based on fragment size, the BDFFP data indicate that 1‐ and 10‐ha fragments have similarly depauperate understory bird communities after fragment isolation (Stouffer & Bierregaard, 1995). Recent studies that focused on long‐term effects of fragment isolation disturbance on the understory bird community in the BDFFP study area in terms of abundance and community composition (Stouffer et al., 2021) and bird biomass and ecological function (Luther et al., 2022) lumped 1‐ and 10‐ha fragments. Under the ecosystem decay hypothesis, fragment isolation affects the ecological processes of the fragment regardless of its size.…”
Section: Methodsmentioning
confidence: 99%